The Phenomenon of Catcalling as an Act of Sexual Harassment among Students - Anhar, Tyko Abadi; Haryanti, Yanti (Universitas Muhammadiyah Surakarta, 2023)
Verbal sexual harassment (catcalling) is a type of symbolic sexual harassment that is still normalized or tolerated among the public or students. The public, especially students, still do not recognize catcalling as verbal sexual harassment, let alone those who encourage the perpetrators of verbal sexual harassment. Researchers obtain a problem formulation, namely. What are the factors that encourage perpetrators to carry out catcalling in the university environment? The aim of this research is to identify the factors behind catcalling on campus. The subjects of this research are divided into two, namely. informants as perpetrators and informants as victims. This research was structured based on qualitative methods with the aim of understanding a phenomenon that occurred in depth using a phenomenological approach and using the theory of Pierre Bourdieu and Verbal and Non-Verbal Communication. The aim of this approach is that researchers want to understand more about the experiences, perceptions, behavior, actions and motivations of informants. The data collection techniques used were observation, interviews and supporting documentation. The results of research in the field are from analysis of arena, habitus, power and capital as well as verbal and non-verbal messages resulting in field findings that the symbolic meaning of each informant does not just happen, there are similarities and differences according to the experience of each informant. Differences in communication methods, backgrounds, arenas and habitus are also factors that encourage verbal sexual harassment to occur in the university environment. The impact felt by each informant regarding catcalling included the positive impact felt by the informant as the perpetrator of catcalling, no impact whatsoever for some informants and the negative impact experienced by the informant as a victim of catcalling.